Causal effects of education attainment on oral and oropharyngeal cancer: New evidence from a meta-analysis and Mendelian randomization study - Chen, Gui; Xie, Junyang; Liu, Di; Zhang, Xiaowen; Tang, Anzhou (Frontiers in Public Health, 2023)
Objectives Higher educational attainment (EA) has proven to be beneficial for preventing and treating various types of cancers. Currently, there is little evidence on the association between EA and prevention of oral cavity and pharyngeal cancer (OCPC). Methods Several databases were searched until October 1, 2022, and a meta-analysis was performed. A Mendelian randomization (MR) study was conducted with EA (i.e., the exposure) data derived from the Social Science Genetic Association Consortium and 6,034 cases of OCPC (i.e., outcome) selected from the Integrative Epidemiology Unit genome-wide association study. Five methods were used to evaluate the causality between EA and OCPC. The leave-one-out sensitivity test, MR-Egger regression, and multivariable MR (MVMR) analysis were applied to evaluate the MR results. Results The meta-analysis included 36 eligible studies. EA was significantly and negatively associated with OCPC risk (odds ratio [OR]: 0.439, 95% confidence interval [CI]: 0.383–0.503, P < 0.001). MR analysis revealed that the risk of OCPC, oropharyngeal cancer, and oral cavity cancer decreased with an increase in education (OR: 0.349, 95% CI: 0.222–0.548, P < 0.001; OR: 0.343, 95% CI: 0.198–0.597; P < 0.001; OR: 0.342, 95% CI: 0.195–0.601, P < 0.001, respectively). Even after correcting for mediators, high EA still significantly reduced the risk of OCPC (OR: 0.361, 95% CI: 0.281–0.463, P < 0.001). Conclusion Both the meta-analysis and MR results demonstrated that high levels of EA can reduce the risk of OCPC in the general population.